ELDERLY HEALTH POLICY: INITIATIVES VERIFIED IN THE CITY OF CITY OF RIO GRANDE-RS - Cenir Gonçalves Tier; Michele Salum Bulhosa; Maria Cristina Flores Soares; Silvana Sidney Costa Santos; Ana Luiza Muccillo Baisch; Maria Elizabeth Cestari (Universidade Federal do Paraná, 2006)
Exploratory descriptive/reflexive research, with secondary data gathered through information on the elderly population and identification of activities carried out with the elderly. The aim was to get to know the implementation of the National Elderly Health Policy in Rio GrandeRio Grande do Sul State. Data were compared to what is proposed by Bill 1395/99 which rules over the Elderly National Health Policy, being identified: in the field of Health Promotion and Maintenance of FunctionalAbility, influenza and tetanus vaccination, the Third Age University Group, Peer Groups and other initiatives of the Elderly Support Program; home care in the field of Support to the Elderly Health Needs through the Family Health Program; in the field of Support to the Development of Informal Care, the Peer Group for families of the elderly suffering from Alzheimer; in the field of Study and Research Support, the Group of Study and Research on Geriatric Nursing; in the field of human resource qualification, specific disciplines on elderly health (Nursing graduation and masters degree at FURG) and the course on awareness to the elderly care. Actions were evidenced although they are disarticulated and hampered by human and financial resources.